Implementasi Deteksi Warna Pada Game Finding Color Menggunakan Ekstraksi Fitur Warna dan Fuzzy Decision Tree - Risna Hasanah; Eka Wahyu Hidayat; Neng Ika Kurniati (Maranatha University Press, 2020)
Recognizing color is an ability that must be trained from an early age. But the ability to recognize color in early childhood is still low. One of the most preferred media by children is games. Android mobile games have the advantage of providing interactive multimedia, challenges, and rewards. Finding Color games can be used to help children play actively in exploring and observing colors in the surrounding environment because they can detect colors using the camera. The stages in color detection in games are feature extraction and color classification. Color feature extraction will get the color value at the selected pixel coordinates on the screen. The color classification uses fuzzy decision tree ID3. The test results of the application of color feature extraction produce an accuracy value of 100%. The fuzzy decision tree classification is evaluated using a confusion matrix, resulting in an accuracy value in outdoor light conditions of 94.4%. There is an increase of 4.4% compared to indoor conditions. Keywords— Color Detection; Color Feature Extraction; Fuzzy Decision Tree; Game; Mobile Android